2008
DOI: 10.1590/s0101-98802008000300006
|View full text |Cite
|
Sign up to set email alerts
|

Influência da irrigação de soluções nutricionais no colo excluso de trânsito intestinal: estudo experimental em ratos

Abstract: RESUMO: A colite por exclusão é descrita como processo inflamatório que ocorre nos segmentos colorretais desprovidos do trânsito fecal. A deficiência dos ácidos graxos de cadeia curta vem sendo considerada como principal fator causal. Objetivo: O objetivo do presente estudo foi avaliar, em modelo experimental de colite de exclusão, a importância da irrigação do segmento desprovido de trânsito com soluções nutricionais na prevenção e tratamento do processo inflamatório. Método: Foram utilizados trinta ratos Wis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 21 publications
2
17
0
2
Order By: Relevance
“…Studies have shown that fecal stream restoration reverts the disease symptoms in most cases, making it the most effective therapy for the prevention of DC 13 .However, fecal traffic recovery is not always possible, which promotes the evaluation of other therapeutic strategies 20 . As the pathogenesis of DC is related to deficient supply of SCFAs, the most obvious strategy is to apply enemas with SCFAs in the segment without fecal stream 18,19,33,34 . A series of studies confirmed that the irrigation of segments without fecal stream with SCFAs-rich solutions, particularly butyrate, can revert endoscopic and histological alterations related to the disease and reduce the levels of tissue oxidative stress [9][10][11][12][13]15,17,18,33,34 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that fecal stream restoration reverts the disease symptoms in most cases, making it the most effective therapy for the prevention of DC 13 .However, fecal traffic recovery is not always possible, which promotes the evaluation of other therapeutic strategies 20 . As the pathogenesis of DC is related to deficient supply of SCFAs, the most obvious strategy is to apply enemas with SCFAs in the segment without fecal stream 18,19,33,34 . A series of studies confirmed that the irrigation of segments without fecal stream with SCFAs-rich solutions, particularly butyrate, can revert endoscopic and histological alterations related to the disease and reduce the levels of tissue oxidative stress [9][10][11][12][13]15,17,18,33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…As the pathogenesis of DC is related to deficient supply of SCFAs, the most obvious strategy is to apply enemas with SCFAs in the segment without fecal stream 18,19,33,34 . A series of studies confirmed that the irrigation of segments without fecal stream with SCFAs-rich solutions, particularly butyrate, can revert endoscopic and histological alterations related to the disease and reduce the levels of tissue oxidative stress [9][10][11][12][13]15,17,18,33,34 . The main action of SCFAs in the segment without fecal stream would be to restore homeostasis in the reactions that promote energy production by the cells, preventing the excessive formation of OFRs and, consequently, the tissue oxidative stress 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A irrigação intestinal com butirato e propionato de sódio diminuiu o processo inflamatório e favoreceu a epitelização da mucosa cólica, em ratos com colite induzida por ácido acético, quando comparado a aplicação de clisteres com soluções ricas em glicose ou solução salina 10,26 . De modo contrário, a exposição da mucosa cólica a substâncias oxidantes, tais como o H 2 O 2 , por aumentar a peroxidação dos fosfolipídeos das membranas celulares, aumenta o processo inflamatório local 27 .…”
Section: Discussionunclassified
“…Essa possibilidade é reforçada ao se constatar que a reconstituição do trânsito, ou a irrigação dos segmentos exclusos com soluções nutricionais ricas em AGCC, restabelecendo o substrato energético à mucosa cólica, são capazes de reverter as alterações clínicas e histopatológicas encontradas nos portadores de CE [9][10][11] . Os AGCC são formados a partir da fermentação de carboidratos não absorvidos pelo intestino delgado pela flora bacteriana do interior do cólon.…”
Section: Introductionunclassified